2011
DOI: 10.1111/j.1745-4549.2011.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Lycopene by Gelatin-Pectin Complex Coacervation

Abstract: The aim of this work was to produce and characterize microcapsules of lycopene and to evaluate their stability in comparison with free lycopene. An oily dispersion of lycopene was encapsulated by complex coacervation using gelatin and pectin. Samples were analyzed at four different pH values (3, 3.5, 4 and 4.5) and three proportions of core (25, 50 and 100%). The moisture, water activity, solubility, hygroscopicity, encapsulation efficiency and stability of lycopene microcapsules kept at 10 and 25C were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 21 publications
3
58
1
7
Order By: Relevance
“…As an antioxidant, Lyc has a singlet-oxygen-quenching ability that is twice that of b-carotene and 10 times higher than that of atocopherol (Silva et al 2012). However, some studies have shown that encapsulation techniques increase the stability of Lyc in the presence of oxygen, heat, and light (Chiu et al 2007; Goula and Adamopoulos 2012;Montenegro et al 2007;Blanch et al 2007).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As an antioxidant, Lyc has a singlet-oxygen-quenching ability that is twice that of b-carotene and 10 times higher than that of atocopherol (Silva et al 2012). However, some studies have shown that encapsulation techniques increase the stability of Lyc in the presence of oxygen, heat, and light (Chiu et al 2007; Goula and Adamopoulos 2012;Montenegro et al 2007;Blanch et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Carotenoids may also serve as antioxidants and free-radicalquenching agents. They interact with free radicals and oxygen, inhibiting the propagation step of lipid peroxidation (Silva et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The disc containing specimens was placed in vacuum sublimator sputter coater (JFC -1600, JEOL, Germany) and sprayed with platinum. The stub was placed on a pre-cryogenic electron microscope specimen holder that was pre-frozen by liquid nitrogen and observed at acceleration voltage 10kV and 20kV (Silva et al 2012). …”
Section: Sem Analysismentioning
confidence: 99%
“…It reduces low-density lipoprotein oxidation and helps lower cholesterol levels in the blood. In addition, lycopene can reduce the risk of developing macular degeneration, serum lipid oxidation and cancers of the lung, bladder, cervix and skin (Rao and Agarwal 1999;Silva et al 2012). The properties, actions and functions of carotenoids, including lycopene, are closely related to their geometric isomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation